Correlate of Bar Product Mix and Customer Retention in Rivers State, Nigeria: An Empirical Investigation - ETUK, Joseph .S; NZEI, Justina, A (Zien Journals, 2025)
The Commercial bar sector has not attracted adequate empirical investigations despite its rising status as a fast-growing sub-sector of the hospitality industry contributing significantly to national and global GDP. This study, therefore, investigated bar products mix and customer retention in Port Harcourt, Rivers State, Nigeria. The cross sectional survey research design was adopted for the study whereby data were collected from 136 bar customers in Port Harcourt, Rivers State through the questionnaire method. Descriptive analytical tools of frequencies, percentage, mean score and standard deviations were used for demographic data and univariate analysis. Bivariate analysis (test of hypotheses) was performed using the Pearson Product Moment Correlation analytical technique, aided by the Statistical Package for Social Sciences (SPSS), version 21, tested at 5% (0.05) level of significance. The study revealed that bar product mix (varieties of local cuisines, car wash service, sport view entertainment and service delivery) were significant variables that affected customer retention in the local bars surveyed in Port Harcourt. On the basis of the findings, the study concluded that varieties of native food and beverages, car wash services, sport view entertainment and effective service delivery had a positive and significant correlation with customer retention through loyalty and referrals to the local bars surveyed. Based on the findings and conclusion of the study, it was recommended that managers of the bars should maintain or improve on the integrated bar services by ensuring availability of the varieties of products at all times, customer service and exploring opportunities for innovative products/services and training of service personnel for improved service delivery for sustainable customer retention.
Keywords: Bar Product Mix; Customer Retention